DEPRIVASI RELATIF KOMPETENSI KEPEMIMPINAN GURU PAI: Kajian Komparatif Guru Akidah Akhlak Berkualifikasi S1 dan Guru Tugas Pesantren Lulusan MA - Zumrotul Mukaffa (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2018)
This paper attempts to examine the leadership competence of Islamic Religious Education (Pendidikan Agama Islam/PAI) teachers in the areas of Islamic theology and Morality with the qualification of Bachelor Degree (S1) and pesantren-assigned teachers (guru tugas pesantren) graduated from IslamicSenior High School and factors that influence it. PAI teachers with the qualification of S1 or those who have pedagogical competence are believed to have higher leadership competencies, and vice versa,pesantren-assigned teachers with secondary level education qualification, have lower leadership competence. The results show a contrasting real picture of the phenomenon. This reality is interesting to examine further in order to find the pattern to increase the competence of teachers in accordance with the needs of madrasahs/schools. This study uses a combination of methods, quantitative supported by the analysis of qualitative data (mix-methods) by taking the population of Islamic Theology and Morality teachers who teach in Madrasah Ibtidaiyah (MI). The results of the analysis illustrate the average value of the competence of PAI teachers with S1 qualification which is 55.8333 and pesantren-assigned teachers which is 51.4000 with the mean of difference 4.43333. Although there is an average difference, it is not so significant. The level of significance is only 0.040 which means <0.05. Based on the statistical calculation, there is no difference in leadership competence among S1 graduated teachers and pesantren-assigned teachers. Qualitative data analysis shows that there are structural factors that negatively affect the achievement of the competence of PAI teachers with S1 qualification. On the other hand, the positive achievement of leadership competence of pesantren-assigned teachers is influenced by the success of technical guidance, strict recruitment, and habituation as peer teacher while they were in pesantren. There is a relative deprivation phenomenon that emerged among PAI teachers who have had academic competence. The various structural policy packages issued by the government that is ideally projected to improve competence, including the leadership competence of the teachers, have a negative impact in the implementation realm. In particular, policies highlight more on improving learning administrative governance aspects which result in a decrease of teachers creative ability in learning.